2004
DOI: 10.1242/dev.01368
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of protein tyrosine phosphatase nonreceptor type 13 in the control of oocyte meiotic maturation

Abstract: Protein tyrosine phosphatase nonreceptor type 13 (PTPN13) is a tyrosine phosphatase with multiple interacting domains that has been implicated previously in the regulation of apoptosis. We provide evidence that PTPN13 plays an important role in the control of the meiotic cell cycle. A cDNA coding for PTPN13 was isolated during the screening for the substrate of protein kinase A expressed in mammalian oocytes. PTPN13 is expressed in both mouse and Xenopus oocytes and is a substrate for protein kinase A in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The influence of protein tyrosine phosphatase PTPL1 in cell cycle and proliferation has not been extensively studied. Available data point towards a role in cytokinesis in HeLa cells [8] and in meiosis in Xenopus oocytes [9]. We have shown here that downregulation of endogenous PTPL1 by siRNA induces changes in cell cycle profile.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The influence of protein tyrosine phosphatase PTPL1 in cell cycle and proliferation has not been extensively studied. Available data point towards a role in cytokinesis in HeLa cells [8] and in meiosis in Xenopus oocytes [9]. We have shown here that downregulation of endogenous PTPL1 by siRNA induces changes in cell cycle profile.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, PTPL1 overexpression induces defects in cytokinesis. Also, it has been shown that PTPL1 functions downstream of cAMP signaling and plays an essential role in controlling meiotic resumption in Xenopus oocytes [9]. In relation to invasion, there are several reports addressing a role of PTPL1 in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, several genes from this group are directly involved in cell differentiation. PTPN13 is a proapoptotic protein tyrosine phosphatase, which is overexpressed in most cancer cells, and is involved in the regulation of cell differentiation (49). The expression pattern of CCNB1 is markedly different among differentiated lung cancers (11).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PTPL1 has been implicated in the regulation of cytokinesis in HeLa cells, 32 and in the control of the meiotic cell cycle, 33 clearly supporting its importance in cell growth regulation. More recently, Zhu et al 34 demonstrated that PTPL1 can inhibit HER2/Neu, a signaling pathway that is frequently deregulated in breast cancer.…”
mentioning
confidence: 81%